Association of promoter polymorphism −765G>C in the PTGS2 gene with malignant melanoma in Italian patients and its correlation to gene expression in dermal fibroblasts. Issue 10 (October 2014) - Gomez‐Lira, Macarena; Ferronato, Silvia; Malerba, Giovanni; Santinami, Mario; Maurichi, Andrea; Sangalli, Antonella; Turco, Alberto; Perego, Paola; Rodolfo, Monica
Abstract Prostaglandins, especially prostaglandin E synthetase (PGE2), influence carcinogenesis by promoting cell proliferation, inhibiting apoptosis, stimulating angiogenesis and mediating immune suppression. Cyclooxygenase‐2, coded by the PTGS2 gene, is the key enzyme in the production of prostaglandins. In melanoma, Cox‐2 is over expressed in primary malignant melanoma (MM) and in their corresponding metastases. Polymorphisms in the promoter region of PTGS2 gene can modulate gene expression and could modify individual susceptibility to MM. Two hundred and forty melanoma patients and 342 controls were genotyped for polymorphisms −765G>C (rs20417) and −1195A>G (rs689466). Allele −765C frequency was significantly higher in melanoma patients. No allele frequency differences for −1195A>G polymorphism were observed. Haplotype analysis revealed that the haplotypes carrying the minor alleles were associated to a higher risk of melanoma (P = 0.02). Expression analysis showed that allele −765C is associated to a higher gene expression and could represent a risk allele by affecting the functionality of the promoter.